Arabidopsis RAP2.2: An Ethylene Response Transcription Factor That Is Important for Hypoxia Survival(1)([W])([OA]) - Hinz, Manuela (American Society of Plant Biologists, 2010)
Arabidopsis (Arabidopsis thaliana) RAP2.2 (At3g14230) is an APETALA2/ethylene response factor-type transcription factor that belongs to the same subfamily as the rice (Oryza sativa) submergence tolerance gene SUB1A. RAP2.2 is expressed at constitutively high levels in the roots and at lower levels in the shoots, where it is induced by darkness. Effector studies and analysis of ethylene signal transduction mutants indicate that RAP2.2 is induced in shoots by ethylene and functions in an ethylene-controlled signal transduction pathway. Overexpression of RAP2.2 resulted in improved plant survival under hypoxia (low-oxygen) stress, whereas lines containing T-DNA knockouts of the gene had poorer survival rates than the wild type. This indicates that RAP2.2 is important in a plant's ability to resist hypoxia stress. Observation of the expression pattern of 32 low-oxygen and ethylene-associated genes showed that RAP2.2 affects only part of the low-oxygen response, particularly the induction of genes encoding sugar metabolism and fermentation pathway enzymes, as well as ethylene biosynthesis genes. Our results provide a new insight on the regulation of gene expression under low-oxygen conditions. Lighting plays an important regulatory role and is intertwined with hypoxia conditions; both stimuli may act collaboratively to regulate the hypoxic response.